2018
DOI: 10.1027/0227-5910/a000509
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Rates in Evacuation Areas After the Fukushima Daiichi Nuclear Disaster

Abstract: Abstract. Background: Associations between nuclear disasters and suicide have been examined to a limited extent. Aim: To clarify the suicide rates in evacuation areas after the nuclear disaster in Fukushima, which occurred in March 2011. Method: This descriptive study used monthly data from vital statistics between March 2009 and December 2015. Suicide rates in areas to which evacuation orders had been issued, requiring across-the-board, compulsory evacuation of residents from the entire or part of municipalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 27 publications
1
37
0
Order By: Relevance
“…Of the extracted 61 studies, 41 studies (67.2%) assessed emotional consequences (Table 1), whereas 28 studies (45.9%) evaluated behavioral consequences (Table 2). 16,19,29,[32][33][34][35]51,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] Eight studies (13.1%) evaluated both emotional and behavioral outcomes. 16,19,29,[32][33][34][35]51 Nearly half (n = 30, 49.2%) of the studies used community data.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the extracted 61 studies, 41 studies (67.2%) assessed emotional consequences (Table 1), whereas 28 studies (45.9%) evaluated behavioral consequences (Table 2). 16,19,29,[32][33][34][35]51,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] Eight studies (13.1%) evaluated both emotional and behavioral outcomes. 16,19,29,[32][33][34][35]51 Nearly half (n = 30, 49.2%) of the studies used community data.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…64 Three studies (4.9%) used government statistics data and made prepost disaster comparisons for each study. 46,65,67 Two studies (3.3%) used medical record data acquired immediately after the disaster. 53,56 A study reporting intervention methods or effects was not included in the present review.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Mental health has also been affected by the loss of employment and/or community ties due to the nuclear disaster and subsequent residential relocation, with consequent drastic changes in living circumstances [ 9 ]. It is possible that these situations have led to the increased suicide rates in the evacuation area [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although no Japanese study has investigated whether people have experienced changes in social connectedness during the pandemic, a study in the United Kingdom in June 2020 found that 47%, 45%, and 31% of survey respondents felt more connected with their family members, neighbors, and local community, respectively, during lockdown (Abrams et al, 2020). Studies on the effect of natural and human-induced disasters on suicide (Matsubayashi et al, 2013;Orui et al, 2018;Safarpour et al, 2020) show that suicide rates tend to rise after a large disaster (Safarpour et al, 2020), but can temporarily drop after a natural disaster, as long as the scale of the disaster is not very large (Matsubayashi et al, 2013). This is because social integration tends to increase after natural disasters, which can protect against suicide risk (Matsubayashi et al, 2013).…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%